BLOOD PROFILE OF GUINEA FOWL (Numida meleagris ) FED VAERYING LEVELS OF PROTEIN AND ENERGY (Journal of Veterinary Medicine and Animal Production, 2022)
Blood profile of 150 day old helmeted guinea fowl (Numida meleagris galeata) keets was  studied. They were grouped into 5 dietary groups of varying levels of protein and energy .Clotted and un-clotted blood samples were collected at 8 weeks on slaughter and examined on the same day. Parameters measured included Hb ,PCV ,WBC counts ALP, CK, AST, LDS, sugar creatinine ,total protein ,albumin, Na, P, Ca and K. Significant increase in P, albumin, Ca, PCV levels were detected when low protein high energy diet was fed. Significant increase in creatinine was associated with high protein high energy diet and in Ca when low protein low energy diet was fed
Keywords: Guinea; Fowl; Haematology; Metabolites; Electrolytes; Enzymes